Correlation of cervical vertebral maturity and teeth calcification stages in children with cleft lip and palate - Sandy Pamadya; Azhari Azhari; Ria Noerianingsih Firman (Majalah Kedokteran Gigi Indonesia, 2018)
Cleft lip and palate are the most common craniofacial anomalies in Indonesia. Recent publications report that there was delayed skeletal and dental age in cleft lip and palate patients. Panoramic and lateral cephalometric radiograph to evaluate growth and development through skeletal and dental age is still rarely used. The research aimed to determine the correlation between cervical vertebral maturation and teeth calcification stages in children aged 7 to 16 years old with cleft lip and palate in Unpad Dental Hospital. The research design was analytic correlation and the sample was selected using purposive sampling cross-sectional using secondary data panoramic and lateral cephalometric radiograph. The scores of cervical maturation and teeth calcification stages were then analyzed statistically using SPSS version 16. Spearman coefficient of rank correlation test showed strong correlation between cervical vertebral maturation and teeth calcification stages on all teeth, with the highest rs score was secondary molar (0.734) and p value 0.000 The conclusion of this research is that there is a strong correlation between cervical vertebral maturation and teeth calcification stages in children aged 7 to 16 years old with cleft lip and palate.